Determinant factors for chronic kidney disease after partial nephrectomy. (2018)
The objective of this review is to evaluate the factors that determine the development or deterioration of Chronic Kidney Disease (CKD) after partial nephrectomy (PN). When current literature is reviewed, it is found that factors that influence renal function after partial nephrectomy, are multifactorial. Those are divided into pre-surgical factors, such as hypertension, diabetes mellitus, urolithiasis, obesity, metabolic syndrome among others; intra-surgical factors, like the surgical technique used, the remaining healthy tissue, the experience of the surgeon, the time and type of ischemia among others. Lastly, post-surgical factors, also impose some influence on the post-surgical renal performance. It was also found that minimally invasive surgery, in addition to its known advantages, seems to offer a greater field of action in the future that will allow more nephrons preservation in any future surgical scenario. Finally, the current trend is to perform PN on all patients, in whom surgery is technically feasible regardless of the approach used, without risking oncological outcomes, patient safety, and without being exposed to any additional complications.